Interdisciplinarity: History, theory, & practise - Klein, Julie (Detroit Wayne state University Press, 1990)
In this volume, Julie Klein provides the first comprehensive study of the modern concept of interdisciplinarity, supplementing her discussion with the most complete bibliography yet compiled on the subject. Spanning the social sciences, natural sciences, humanities, and professions, her study is a synthesis of existing scholarship on interdisciplinary research, education and health care.Klein argues that any interdisciplinary activity embodies a complex network of historical, social, psychological, political, economic, philosophical, and intellectual factors. Whether the context is a short-ranged instrumentality or a long-range reconceptualization of the way we know and learn, the concept of interdisciplinarity is an important means of solving problems and answering questions that cannot be satisfactorily addressed using singular methods or approaches.